Form Follows Familiarity : Proposing a Design Paradigm for Architecture in the Metaverse - Atta Idrawani, Zaini; Nadzirah, Jausus; Mohd Zariq Feeqri, Jasni; Mohamed Rashid, Embi (Springer, 2024)
The acceleration of the digitalization process during the COVID-19 pandemic has led to a mass interest in Web 3.0, blockchain, and the metaverse, where digital assets are given a new sense of authenticity. Academic discourses seem to envision architecture in the same light, by acknowledging standardization of architecture to redeem its authentic place in the metaverse. It is argued that it needs to be further reduced into a design paradigm, where ‘form follows familiarity’ is proposed. This study employed visual surveys on ‘Decentraland’ and ‘Voxels’ platforms in identifying familiarity variables, which are reduced versions of buildings’ recognizability variables in the real world. It is observed that architectures in the metaverse act as an avatar and are mostly independent from architectural consciousness, but the sense of familiarity has a major impact on its form as they are constantly noticeable from the visual surveys. This study found that the design paradigm ‘form follows familiarity’ has already been embedded in the ‘metaversal’ thinking of architecture but just with various degrees of negotiation and conscious intentions. ‘Form follows familiarity’ also carries with it a philosophical indication for understanding the existential fate of architecture represented in a different world which shares similar stakes of authenticity, scarcity, and ownership with the real world. It is advocated that more studies to continue understanding this unique place of architecture in the metaverse.